1972
DOI: 10.2134/agronj1972.00021962006400020009x
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides vs Oat Companion Crops for Alfalfa Establishment1

Abstract: Herbicides are effective for use in establishing alfalfa (Medicago sativa L.) without the use of a companion crop. The objective of the study was to assess the economic feasibility of the herbicide method as compared to the companion crop method and to determine some of its advantages and disadvantages. Productivity of ‘Vernal’ alfalfa established with or without a companion crop was determined at four locations in Minnesota. Oats (Avena sativa L.), harvested for either hay or grain, was used as the companion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
6
18
1
Order By: Relevance
“…Total forage yields for the two harvests made in the year following establishment did not differ among treatments at either location (Table 1). This result is consistent with the results of a number of other alfalfa establishment studies in which various companion crop and herbicide treatments were compared (Brothers et al, 1994; Curran et al, 1993; Schmid and Behrens, 1972).…”
Section: Resultssupporting
confidence: 90%
“…Total forage yields for the two harvests made in the year following establishment did not differ among treatments at either location (Table 1). This result is consistent with the results of a number of other alfalfa establishment studies in which various companion crop and herbicide treatments were compared (Brothers et al, 1994; Curran et al, 1993; Schmid and Behrens, 1972).…”
Section: Resultssupporting
confidence: 90%
“…Seeding rates of 0, 60, 120 and 180 kg ha )1 in the companion crop produced 3294, 4451, 4718 and 5131 kg ha )1 hay yield, respectively. These results are similar to those of Schmid and Behrens (1972), who also obtained greater hay yields in the seeding year when the companion crop was harvested at the early dough stage compared with solo sowings. Latta and Blacklow (2001) found that sowing barley at higher rates increased yield compared with low seeding rates in the establishment year.…”
Section: Resultssupporting
confidence: 86%
“…These less vigorous plants, in western Canada, tend to produce less forage in the establishment year (year 1) and in the subsequent year (Waddington and Bittman 1983). However, in climates that are warmer than western Canada, forage plants seem to recover from initial stress during the fall of year I and stands established with or without companion crops produce similar yields in year 2 (Hansen and Krueger 1973;Klebesadel and Smith 1960;Schmid and Behrens 1972). Genest and Steppler (1973) (Jeffersen et al 1983).…”
mentioning
confidence: 99%